External financing and economic activity in the euro area: Why are bank loans special? - I\~naki Aldasoro; Robert Unger (Deutsche Bundesbank, 2017)
Using a Bayesian vector autoregression (BVAR) identified with a mix of sign and zero restrictions, we show that a restrictive bank loan supply shock has a strong and persistent negative impact on real GDP and the GDP deflator. This result comes about even though flows of other sources of financing, such as equity and debt securities, expand strongly and act as a "spare tire" for the reduction in bank loans. We show that this result can be rationalized by a recently revived view of banking, which holds that banks increase the nominal purchasing power of the economy when they create additional deposits in the act of lending. Consequently, our findings indicate that a substitution of bank loans by other sources of financing might have negative macroeconomic repercussions.
Keywords: E30; E40; E50; G20; G30; 330; bank loans; Bayesian VAR; credit creation; ECB; euro area; external financing; financing structure